أثر استخدام خرائط المفاهيم في اكتساب المفاهيم المتعلقة بمقرر الصرف لدى طالبات المستوى السادس بجامعة الرية - Neneng Komariah; Arawati (Rayah Al-Islam, 2019)
The aim of the research was to The Effect of Using Mind Mapping on the 6th College Students in Mastery of Concept Related to Shorof Module of STIBA Ar-Raayah. In this research, the researcher chose random sampling by taking two class, the researcher took 30 college students as the sample. There were 15 in experimental class and 15 in controlled class. Experiment class was taught by mind mapping, while controlled class was taught without mind mapping (traditional method). The research conducted quantitative research by applying quasi experimental research with this method the writer can find out the effect of using mind mapping on the 6th college students in Mastery of Concept Related to Shorof Module of STIBA Ar-Raayah, the researcher practices learning by using mind mapping accompanied by examinations for each group, and then the researcher describes the results of her research. This research had shown that there are differences in exam results between the experimental class and the control class, where the results of the experimental class got (1,140) with percentages (75.93%) and the control class results got (1,080) with percentages (71.84%) and differences between both (60) with percentage (4.09%).